Vielfältig statt ideal: Arbeitspsychologisches Feldexperiment zur Gestaltung von Nutzerarbeitsplätzen in einer Universitätsbibliothek - Ebert, Katharina; Waßmann, Stefan (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2021)
This paper presents a psychological study, which examined four different work spaces in the university library of the Otto-von-Guericke-University Magdeburg based on the learning environment evaluated by students. The study was commissioned by the library with the aim to identify important factors in designing a learning environment, which fits the students` needs. Based on similar studies conducted in other university libraries the environmental perception and the evaluation of the workspaces were examined with questionnaires and standardised interviews. A mobile eye-tracking system was used to analyse potential distractors around the spaces. The results show that the perceived features of the learning environment have an impact on the wellbeing of the students, which in turn influences the choice of their favourite learning space. Based on the interpretation of these findings and taking into account possible limitations of the study design the data indicate that light, ergonomic features and the visibility of the whole room as well as noise have an important influence on the wellbeing of students. However, because of individual learning preferences, users prefer different learning spaces. Therefore there cannot be the perfect learning space. The results indicate that university libraries should focus on providing a diverse choice of learning spaces.